The Role of Λ-Effective Mass in a Phenomenological Analysis of the Λ-Energy in Hypernuclei - Efthimiou, C. A.; Grypeos, M. E.; Koutroulos, C. G. (HNPS Advances in Nuclear Physics, 2020)
A preliminary account is given of an effort undertaken to allow for the effective mass of the Λ-particle in a phenomenological analysis of existing experimental data for the (ground state) energy of the Λ : EΛ in hypernuclei. The non - relativistic treatment is adopted to describe the motion of the Λ - particle, by considering a central potential well V (r), formed by the nuclear "host" medium of the Λ in the hypernucleus. The Λ - effective mass in the medium is taken to be an r-dependent effective mass mΛ(r) representing approximately some non-local effects in a way suggested in the past. Certain preliminary numerical results are obtained and discussed.